INSTITUTIONAL AND POLICY DEVELOPMENT IN ISLAM - Nurhidayat, Naufal; Ulpah, Dina Mariana; Nugraha, Hanafi; Sunengsih, Imas (Komitmen: Jurnal Ilmiah Manajemen, 2025)
This journal examines Islamic development institutions and policies. It aims to learn more about Islamic institutional and development policies in ensuring that the interests of society are aligned with the principles of Shari’a. The method used in this journal is a qualitative approach obtained from the literature of books, articles and the internet and refers to previous research that is collaborated into related discussions so that the author can provide systematic and relevant conclusions. The results of this journal state that institutions and policies have a relationship in development, especially the country’s economy, which is realized through special institutions related to public welfare, such as shari’a banking, shari’a pawn shops, BAZNAS, BMT. In Islam, economic development is not only a physical necessity, but is oriented towards spiritual development through aspects of tawhid, khalifah politics, tazkiyah, and physical development.